Telecommunication Mergers and Acquisitions: An Event Study Analysis - Agarwal, Hemant (2009)
The change in global communications in the past decade has been remarkable, bringing fundamental changes in the structure and the regulation of telecom markets worldwide. Leading edge technology and liberal telecom solutions have caught the eye of several telecommunication manufacturers, service providers, and operators. There are studies that report only the acquiring firm’s returns or the target firm’s returns. Some of them report the abnormal returns for the combined acquiring and target firm’s shareholders. The acquiring firm is the one that wants to acquire another firm, and the target firm is the one that risks being acquired. My research aims to measure the abnormal returns of the acquiring firm due to the announcement of a merger. For this purpose an Event study was undertaken on a sample consisting of 88 telecommunication mergers in the USA and the UK in the past 10 years. The results yielded that the acquiring firm does experience some positive returns due to the announcements of mergers. Method of payment as a factor for change in the returns was also examined in this report, the results yield that mixed and cash transactions are beneficial whereas stock transactions result in negative returns for the acquirer.